Aktivitas Antijamur Kitosan Dari Cangkang Kerang Bambu (Solen corneus) Pada Pembuatan Hidrogel Terhadap Trichophyton mentagrophytes - Hasibuan , Nabila Hasim; Ridwanto, Ridwanto; Nasution , Haris Munandar; Rani , Zulmai (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Hydrogels are topical preparations applied to the skin surface. Chitosan, a compound derived from the deacetylation of chitin, has various benefits, including antifungal activity. Utilizing waste from bamboo clam shells (Solen courneus) collected in Belawan waters as a source of chitosan could provide a sustainable solution for developing antifungal hydrogel formulations. Objective: This study aimed to produce chitosan from bamboo clam shells, formulate it into a stable hydrogel, and evaluate its antifungal activity against Trichophyton mentagrophytes. Methods: This experimental study involved isolating chitosan through deproteinization, demineralization, depigmentation, and deacetylation steps. The resulting chitosan was characterized by moisture content, ash content, yield, solubility, and functional group identification using FTIR spectroscopy. Subsequently, chitosan was formulated into four hydrogel variations (0%, 2%, 4%, and 6%). The hydrogel formulations were evaluated for organoleptic properties, homogeneity, pH, viscosity, spreadability, adhesiveness, and antifungal activity. Results: The produced chitosan exhibited functional groups similar to standard chitosan and a degree of deacetylation of 77.5%. Hydrogel evaluation over three weeks showed good stability, with pH values of 4–6.5, spreadability of 5–7 cm, adhesiveness greater than 1 second, and viscosity ranging from 3,000–50,000 cps, all meeting the required standards. The antifungal test demonstrated that the 6% chitosan hydrogel had the highest inhibition zone (11.5 mm) against Trichophyton mentagrophytes. Conclusion: Chitosan derived from bamboo clam shells was successfully formulated into a stable hydrogel with effective antifungal activity. The 6% concentration exhibited the strongest antifungal effect, indicating its potential as a topical preparation for treating skin fungal infections.